2017
DOI: 10.1128/aem.00244-17
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Analysis of an Environmental Slurry and Its Potential Role as a Reservoir of Bovine Digital Dermatitis Pathogens

Abstract: At present, very little information exists regarding what role the environmental slurry may play as an infection reservoir and/or route of transmission for bovine digital dermatitis (DD), a disease which is a global problem in dairy herds. To investigate whether DD-related bacteria belong to the indigenous microbiota of the dairy herd environment, we used deep amplicon sequencing of the 16S rRNA gene in 135 slurry samples collected from different sites in 22 dairy farms, with and without DD-infected cows. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…The core bacteria which have been identified in DD lesions are genus Treponema, Mycoplasma, Fusobacterium, Porphyromonas, and Dichelobacter [12,13]. DD-associated Treponema was reported to present in the housing facility of the dairy herds with clinical DD history [14,15]. However, except for traditional pathogens such as Treponema, different bedding materials may selectively promote the survival and growth of other bacterial taxa related to DD lesions.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The core bacteria which have been identified in DD lesions are genus Treponema, Mycoplasma, Fusobacterium, Porphyromonas, and Dichelobacter [12,13]. DD-associated Treponema was reported to present in the housing facility of the dairy herds with clinical DD history [14,15]. However, except for traditional pathogens such as Treponema, different bedding materials may selectively promote the survival and growth of other bacterial taxa related to DD lesions.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…among our samples. Identification of the potential reservoirs for DD Treponema was the main concern in many previous studies (Evans et al 2012(Evans et al , 2016Klitgaard et al 2017). Numerous number of reservoirs for Treponema spp.…”
Section: Dd-associated Treponema Including T Pedis T Medium T Phmentioning
confidence: 99%
“…Further reservoirs and hosts for Treponema have been also documented including non-pedal bovine regions such as oral cavity, bovine rectum, bovine gastrointestinal tract contents, and slurry, confirming the presence of different hosts and environmental reservoirs for Treponema other than the foot tissue or DD lesions. (Edwards et al 2004;Evans et al 2012;Klitgaard et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has also evaluated the role that early or active host‐associated DD lesions play as a primary reservoir of infectious organisms. Multiple studies have demonstrated that the quantitative levels of DD‐associated treponemes are higher in host‐associated tissues (including rectum, gingiva, rumen, DD lesions) than in environmental samples collected from dairy environments (Evans, Timofte et al., ; Klitgaard, Strube, Isbrand, Jensen, & Nielsen, ; Rock, Krull, Gorden, Shearer, & Plummer, ). However, low numbers of DD‐associated Treponema spp can be identified in dairy farm slurry on farms with endemic DD when using deep sequencing‐based phylogenomic approaches (Klitgaard et al., ; Rock et al., ).…”
Section: Transmissionmentioning
confidence: 99%
“…Multiple studies have demonstrated that the quantitative levels of DD‐associated treponemes are higher in host‐associated tissues (including rectum, gingiva, rumen, DD lesions) than in environmental samples collected from dairy environments (Evans, Timofte et al., ; Klitgaard, Strube, Isbrand, Jensen, & Nielsen, ; Rock, Krull, Gorden, Shearer, & Plummer, ). However, low numbers of DD‐associated Treponema spp can be identified in dairy farm slurry on farms with endemic DD when using deep sequencing‐based phylogenomic approaches (Klitgaard et al., ; Rock et al., ). Likewise, there is evidence from multiple groups that foot trimming equipment can be contaminated with treponemes and may act as a source of infection between animals and farms (Rock et al., ; Sullivan et al., ).…”
Section: Transmissionmentioning
confidence: 99%